2023
DOI: 10.1038/s41598-023-28780-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition to smoking in relation to the risk of frailty in ageing

Abstract: Frailty causes emerging global health burden due to its high prevalence and mortality. In this study, we used Mendelian randomization (MR) approach to examine the potential causal relationship between smoking and frailty in ageing. Using inverse-variance weighted (IVW) method, genetically predicted smoking initiation was associated with an increased risk of frailty in ageing (odd ratio (OR) 1.23, 95% confidence interval (CI) 1.19–1.27, P = 3.21 × 10–39). Similarly, per year increase in age of initiation of reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Many studies have reported mixed results when examining the association between smoking and frailty (there are no reports on pre-frailty) [ 20 , 21 ]. The biological mechanisms underlying the relationship between smoking and pre-frailty are not fully understood [ 22 ]. Smoking depresses muscle protein synthesis and induces an elevated expression of myostatin and muscle atrophy F-box (MAFBx), resulting in muscle catabolism [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported mixed results when examining the association between smoking and frailty (there are no reports on pre-frailty) [ 20 , 21 ]. The biological mechanisms underlying the relationship between smoking and pre-frailty are not fully understood [ 22 ]. Smoking depresses muscle protein synthesis and induces an elevated expression of myostatin and muscle atrophy F-box (MAFBx), resulting in muscle catabolism [ 23 ].…”
Section: Discussionmentioning
confidence: 99%